(untitled) (Jalalabad Medical Journal, 2025)
Enterobacter, a genus in the Enterobacteriaceae family, includes 22 recognised species, some of which are linked to health-related infections. Though not all cause diseases, Enterobacter is implicated in hospital-acquired and, to a lesser extent, community-acquired infections like urinary tract infections and soft tissue infections. The aim of the study was to isolate and identify Enterobacter species from different clinical samples and to determine antimicrobial sensitivity patterns. This cross-sectional study conducted in a well-equipped private laboratory in the Sylhet region from January to December 2022 aimed to comprehensively investigate the isolation, identification, and sensitivity patterns of Enterobacter species across various clinical samples. A total of 400 cases with clinical symptoms suggestive of infections were enrolled in the study by purposive sampling. In this study encompassing 400 clinical samples, 71 (17.8%) cases yielded positive cultures of Enterobacter species, with urine samples exhibiting the highest culture positivity rate at 22.2%, followed by wound swabs at 15.5%, and blood at 5%. The predominant species identified were E. Cloacae (76.1%) and E. aerogenes (23.9%). Antibiotic resistance patterns varied, with amikacin and levofloxacin showed the highest sensitivity at 94.4% and 91.6%, respectively, while cefixime and meropenem demonstrated the highest resistance at 69% and 66.2%, respectively. The study highlighted that Enterobacter exhibited diverse responses to different antibiotics, with the highest sensitivity observed for amikacin and levofloxacin, while cefixime and meropenem had the highest resistance. Higher resistence to multiple antibiotics posing challenges in clinical management. Jalalabad Med J 2023; 20 (2): 65-71